Conceptualizing Territorial Mobility through Language of Those who Move and the Dimension of Caste and Ethnicity: From inside a Rural Nepali Community - Subedi, Bhim Prasad (Himalayan Review, 2011)
Available with fulltext. Key words: Territorial mobility; Local conceptualization; Typology; Migration (Basai sarai); Caste and Ethnicity The Himalayan Review Nepal Geographical Society Vol. XXXI 2000 Page: 1-36 Uploaded date: 5 June, 2011